APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) DAN AKUNTABILITAS PENGELOLAAN KEUANGAN DESA - Bagiada, Putu Permana; Hadi, Miftahul (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2023)
This study aims to analyze the implementation of the SISKEUDES application in Dangin Puri Kauh Village, whether it is in accordance with applicable regulations and theories, the benefits of the SISKEUDES application in village financial management, the constraints and obstacles encountered in its implementation and the internal controls applied. This study uses qualitative research techniques with interviews and literature studies. The results of the study show that the implementation of the SISKEUDES application in managing village funds in Dangin Puri Kauh Village is in accordance with applicable regulations, namely Permendagri Number 20 of 2018. The SISKEUDES application also has a role in accountability in managing village funds and managing village finances to become more efficient. The internal control of the SISKEUDES application is also considered quite good. In the implementation in the field there are still obstacles such as slow applications when operating, server down, and other obstacles.